Optimization of hybrid laser and RF inter satellite links in multi-layer low earth orbit (LEO) satellite constellations - He, H.; Balukho, I. N.; Kolchevsky, N. N. (БНТУ, 2025)
The rapid expansion of Low Earth Orbit (LEO) satellite constellations has introduced new challenges in inter-satellite communication. Hybrid architectures combining laser and radio frequency (RF) links are increasingly recognized as a promising solution to balance high throughput, reliability, and resilience. This paper investigates optimization strategies for hybrid laser/RF inter-satellite links in multi-layer LEO constellations. We propose a framework that integrates adaptive link selection, dynamic routing, and cross-layer optimization. Simulation results demonstrate that hybrid link architectures can reduce latency by up to 35 % while maintaining robust connectivity under adverse atmospheric conditions [1][2].